Special Issue: Diversity of Extremophiles in Time and Space - Puente Sánchez, Fernando (2021)
Extreme environments are fascinating ecosystems that have allowed us to increase our knowledge about the evolutionary processes of life [1], develop new biotechnological applications (e.g., industrial applications of lipases [2], and thermostable DNA Polymerases in PCR tests [3]) and establish some fundamental concepts about the origins of life and the search for life in the Universe [1]. Despite the fact that research on the living beings that inhabit these extreme environments (i.e., extremophiles) began more than five decades ago with the pioneering works of Thomas D. Brock [4], nowadays, we still have a lot to learn about microbial diversity, and especially about the metabolism and biochemistry of these microorganisms; therefore, the study of extremophiles, extremozymes and their biotechnological potential remains a hot topic.